Anxiety, language use and linguistic competence in an immigrant context: a vicious circle?. Issue 6 (18th August 2019) - Sevinç, Yeşim; Backus, Ad
ABSTRACT: By exploring two novel concepts, heritage language anxiety (HLA) and majority language anxiety (MLA), this study draws attention to the hitherto neglected topic of language anxiety in immigrant and minority contexts. Based on semi-structured interviews with three generations of Turkish immigrants in the Netherlands ( n  = 30), we investigate why members of an immigrant community experience language anxiety and how it affects them. Findings suggest that language anxiety in the immigrant context, in both its HLA and MLA manifestations, can be attributed to linguistic and socioemotional causes. These linguistic and socioemotional causes, however, are occasionally difficult to isolate and they often interact in bringing about a number of negative consequences. Immigrants may ultimately avoid using the language about which they feel anxious, which will in turn cause further problems in terms of conflicted identities and reduced proficiency in the language concerned. We thus propose that there is a vicious circle that connects bilinguals' language knowledge, language use and language anxiety.